A scoping review of economic evaluations of post-traumatic stress disorder patients’ intervention - Dwarika, Veronica; Amedu, Amos Nnaemeka (International Journal of Public Health Science (IJPHS), 2025)
Intervention programmes for patients with post-traumatic stress disorder (PTSD) have been extensively evaluated economically, and the related implementation costs are presumably high. This study reviewed the cost-effectiveness of PTSD intervention programmes and associated health benefits. The literature search was carried out between June and July 2023. The PRISMA guidelines for scoping review protocols were strictly followed. A literature search was conducted on the National Health Service (NHS) Economic Evaluation Database, PubMed, PsycInfo, and EconLit, this search yielded 16 studies. This review revealed that trauma-focused cognitive-behavioural therapy (+selective serotonin re-uptake inhibitor) (TF+CBT+SSRIs); prolonged exposure therapy; MDMA-assisted therapy (MDMA-AT); stepped care, screen and treatment; and the transmural trauma care model were cost-effective for PTSD treatment. The cost-effectiveness of intervention programmes that lasted 10 to 31 years was greater. In general, long-term intervention programmes have been associated with health benefits. It is also important to note that telemedicine, cognitive-behavioural therapy, biopsychosocial therapy, and individual therapeutic interventions are capital-intensive and inefficient. When disbursing funding for PTSD treatment around the world, the world health organisation (WHO) should keep in mind these identified interventions and the countries where they have been found to be cost-effective.